Cross-sectional survey on environmental pollution surrounding poultry production cluster area - Martindah, E.; Ilham, N. (Diponegoro University, 2019)
This study was carried out to determine the environmental pollution surrounding poultry production cluster (PPC). A cross-sectional survey on environmental pollution surrounding PPC was conducted in the districts of Subang and Ciamis, West Java Province, Indonesia. Information of farmers aspiration on environmental pollution and sanitation issues related to the existence of PPC was collected by semi-structured questionnaires. Ammonia gas (NH3) in feces was tested qualitatively, and ground water was analyzed for Coliform and Salmonella sp. contamination. The result showed that dust and ammonia gases from feces (Subang 300-450 ppm, Ciamis 25-525 ppm) pollute the environment and caused an unpleasant odor surrounding the pens. Fly population was increasing during the harvest time of chickens,causing community daily lives were not comfortable. Water quality surrounding PPC indicated that Salmonella sp. contamination was negligible however most samples from Subang and Ciamis were contaminated with coliform bacteria (<3 MPN/ml–27 MPN/ml). Improvement on management policy to reduce the environmental pollution is thus still needed to develop surrounding the PPC areas.